The role of carbonic anhydrase IX in hypoxia control in OSCC - Pérez-Sayáns, Mario; Supuran, Claudiu T.; Pastorekova, Silvia; Suárez-Peñaranda, José Manuel; Pilar, Gayoso-Diz; Barros-Angueira, Francisco; Gándara-Rey, José Manuel; García-García, Abel (Journal of oral pathology & medicine, 2013)
Tumoral microenvironments play a key role in the evolution of solid tumors. Tumor hypoxia is actively involved in the promotion of genetic instability, the invasive capacity of tumor cells, metastasis, and a worsening of the clinical evolution. Endogenous hypoxia markers are controlled by hypoxia‐related genes, formed by HIF‐1, which is related to several target genes that involve the energy metabolism, angiogenesis, and transmembrane carbonic anhydrases (CAs), mainly CA‐IX that is one of the tumor‐related carbonic anhydrases. The goal of this paper is to establish the role of CA‐IX as a hypoxia marker in OSCC, while analyzing its expression in this type of tumors and its relationship with several clinical and pathological parameters and prognosis, evaluating its relationship with angiogenesis, other hypoxia markers, and clarifying its role in chemotherapy and radiotherapy resistance.